2012
DOI: 10.3746/pnf.2012.17.1.064
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bacillus amyloliquefaciens Strains with Antifungal Activities from Meju

Abstract: Bacilli with fibrinolytic activities were isolated from traditionally-prepared Meju and some of these strains showed strong antifungal activities. One isolate, MJ1-4, showed the strongest antifungal activity. MJ1-4 and other isolates were identified as B. amyloliquefaciens strains by recA gene sequencing and RAPD-PCR results. B. amyloliqufaciens MJ1-4 efficiently inhibited an Aspergillus spp.-producing aflatoxin B1 (AFB1) and a Penicillium spp.-producing ochratoxin (OTA) in addition to other fungi. Antifungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The difference in inhibition efficiency also indicated that media composition has an effect on anti- P. palmivora metabolite production. Although generally, TSB is the richest nutrient composition medium when compared with NB and LB media, and can well support the growth of several bacteria, TSB and NB may interfere with antifungal production as previously observed [ 31 , 32 ]. The original conditions, pH 7 and 37 °C, seemed to be optimal and demonstrated the highest percentage of inhibition when compared with other tested conditions.…”
Section: Discussionmentioning
confidence: 74%
“…The difference in inhibition efficiency also indicated that media composition has an effect on anti- P. palmivora metabolite production. Although generally, TSB is the richest nutrient composition medium when compared with NB and LB media, and can well support the growth of several bacteria, TSB and NB may interfere with antifungal production as previously observed [ 31 , 32 ]. The original conditions, pH 7 and 37 °C, seemed to be optimal and demonstrated the highest percentage of inhibition when compared with other tested conditions.…”
Section: Discussionmentioning
confidence: 74%
“…Activity was expressed as an arbitrary unit (AU) per 1 mL and 1 AU was defined as the highest dilution showing a clear zone of inhibition (16).…”
Section: Methodsmentioning
confidence: 99%
“…Indicators are listed in Table 1. When fungi were used as indicators, potato dextrose agar (PDA) top agar (0.7%, w/v) containing 1x10 5 fungal spores was overlaid on an LB plate (16). Holes were made in plates using a capillary glass tube and 100 µL of FS was placed into each hole.…”
Section: Methodsmentioning
confidence: 99%
“…For sequencing gyrB , primers UP-1 ( ) and UP-2r ( ) were used for gyrB gene amplification, and UP-1S ( ) and UP-2Sr ( ) were used for sequencing [ 70 ]. For sequencing recA , primers rec A-F ( ) and rec A-R ( ) were used for both gene amplification and sequencing [ 71 ]. Each reaction for PCR has a total volume of 25 μl containing 2 μl of ~100 ng/μl of genomic DNA as a template, 2.5 μl of 10X PCR buffer (Agilent Technologies, Inc., Santa Clara, CA), 0.5 μl of 10 mM dNTPs, 0.2 μl of 5 U/μl of Paq5000 DNA polymerase (Agilent Technologies, Inc., Santa Clara, CA), 1 μl of 10 μM of forward and reverse primers, and 17.8 μl of sterilized ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%